Relevansi Ulasan Musik di Media Online dengan Apresiasi Musik Pembaca - Fadli Firdaus; Kiki Zakiah (UNISBA Press, 2023)
Abstract. Technology is currently growing. This has an impact on patterns of human life to be more practical in carrying out daily activities. One of them is in terms of consuming information about music. Various forms of information medium can be used as literature by music lovers. Especially in this digital era, we often encounter music writings milling about in online media. Starting from recommendations for the latest music releases, to scathing criticisms of the ideas of